Improving of the G2C Payment Mechanism as the Part of the Development of the Social Treasury Project Using the Russian National Payment System - S. A. Tomilina; M. L. Dorofeev (Управленческие науки)
The purpose of the study is to consider the possibility of improving the G2C payment mechanism in the context of the digital transformation of the social sphere, as well as to develop a methodological concept for a model for implementing a centralized payment service in the social sphere. The authors reviewed the proposals of Russian and foreign researchers to standardize forms of interaction between citizens and the state. Approaches to understanding the effectiveness of the social security model have been studied; the possibilities for improving state programs for the development of the social treasury and the national payment system have been analyzed; recommendations have been proposed based on the best payment solutions in the field of social security. Based on the results of the study, the authors developed a model of the centralized payment service “SBP ZH”, integrating SBP into the unified state information system for social security (USISSS), which simplifies the “client path” due to simple and convenient identification of beneficiaries of social assistance by phone number. The results of the implementation of the model will be: an increase in the number of recipients of social assistance among residents of populated areas of the country who do not have access to the Internet, and the population of new constituent entities of the Russian Federation (in the context of a lack of payment infrastructure), as well as an increase in the share of non-cash money turnover by 5–6%. The proposed measure for the implementation of the G2C payment mechanism works within the framework of such areas as the Social Treasury project and the Development Strategy of the National Payment System for 2021–2023.